Assessing the use of psychological skills by sports category and the relation with sports performance satisfaction - Tomé-Lourido, D.; Arce, C.; Vales-Vázquez, Á.; Ponte, D. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The evaluation of psychological skills by athletes and their relationship with sports performance and satisfaction has been of great interest in recent decades. Likewise, there has been an emergent tendency to focus on developing specific psychological skills for each sport. The principal aim of this study was to determine the frequency with which athletes deploy psychological skills whilst competing and whether their frequency varies in accordance with the technical, tactical and physical characteristics of the sport in question. A further objective was to establish the connection between the frequency of use of psychological skills and athletes` degree of satisfaction with their performance. METHODS: The study comprised 1003 athletes practicing 43 different sports, grouped into 7 categories based on the similarities between them. Frequency of use of the psychological skills was measured with the Test of Performance Strategies 3. RESULTS: The data analyses allowed the following conclusions to be drawn: the degree to which psychological skills are used is dependent on the technical, tactical and physical characteristics of each sport; and the higher the frequency of the use of psychological skills, the greater the athletes` degree of satisfaction with their performance. CONCLUSIONS: These results allow athletes and coaches to increase levels of sports performance by working on the use of psychological skills, adapted to the technical, tactical or physical requirements of the category in which their sport is included. In addition, working on different psychological skills will improve their satisfaction with sports performance.